Distinguishing Pseudosubluxation From True Injury: A Case of C2-3 and C3-4 Subluxation in a Pediatric Patient. (2nd December 2021) - O'Neill, Conor; Wenzel, Alyssa; Walterscheid, Zakk; Carmouche, Jonathan
Abstract : A 6-year-old girl presented with a one-week history of neck pain after a trampoline accident. Cervical radiographs interpreted as pseudosubluxation of C2 on C3. CT demonstrated the reversal of lordosis with anterolisthesis of C2-C3 and C3-C4. Ten weeks after two months of halo traction, radiographs demonstrated anatomic alignment and maintained disk heights. This case highlights the similarities of pseudosubluxation and true injury, emphasizing the need for high index of suspicion in this population and a successful treatment of subluxation using a halo construct.